A feasibility study: association between gut microbiota enterotype and antibody response to seasonal trivalent influenza vaccine in adults. Issue 3 (29th March 2018) - Shortt, Nick; Poyntz, Hazel; Young, Wayne; Jones, Angela; Gestin, Aurélie; Mooney, Anna; Thayabaran, Darmiga; Sparks, Jenny; Ostapowicz, Tess; Tay, Audrey; Poppitt, Sally; Elliott, Sarah; et al.
Abstract: Objective: We investigated the potential feasibility of a randomized controlled trial of a nutritional intervention that may alter human gut microbiota and support immune defence against respiratory tract infection in adults (Proposed Study). Methods: In total, 125 healthy adults aged 18–64 participated in a 6‐month study that measured antibody response to the seasonal trivalent influenza vaccine. We assessed completion rates, procedure adherence rates and the influence of possible exclusion criteria on potential recruitment into the Proposed Study. We examined whether the gut microbiota could be categorised into enterotypes, and whether there was an association between enterotypes and the antibody response to the influenza vaccine. Results: The participant completion rate was 97.6% (95% CI 93.1–99.5%). The proportions (95% CI) of participants who may be excluded for antibiotic or corticosteroid use in the 30 days prior to the study, or due to receiving the influenza vaccine in the previous two years were 9.6% (5.1–16.2), 8.0% (3.9–14.2) and 61.6% (52.5–70.2), respectively. All participants were stratified into four gut microbiota enterotypes. There was no association between these enterotypes and the antibody response to the influenza vaccine, although the study was not powered for this outcome. Conclusion: This study design is suitable for the Proposed Study. The completion rate is likely to be high, although exclusion criteria should be selected with care. Further analyses of gut microbiota composition or function in association with antibody and immune responses are warranted to explore the role of host–microbiota interactions on protective immunity. Abstract : We have designed a feasible structure for a randomised controlled trial to investigate the efficacy of a nutritional supplement on adult immune responsiveness to the seasonal influenza vaccine. Success will hinge on inclusion and exclusion criteria. We include epidemiological data relating to stool community types and HAI response to the influenza vaccine in New Zealand Adults, which can be used to inform power calculations in future studies.